(3GdeNJUQs - (3MSf Hf SdjeGf GdMdjs ((3Ydi Hf CMeO Hf ESeGYjd GdMSjfj s)
(3ChdgG (B:s
(3PcQ GdTjN GdeajO eMeO Hf eMeO Hf GdfYeGf GdMGQKi aj cJGH GdebGdGJ eG McGjI Gdbhd aj QDjI GdeMJVQ Hf QShd Gddg hCejQ GdeDefjf s
(3BNQgG (B:s
"(3bd dh cGf GdHMQ eOGOkG dcdeGJ QHj dfaP GdHMQ bHd Cf JfaP cdeGJ QHj hdh LFfG HeKdg eOOkG(B" s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdOcJhQ MSjf Ydi eMahX (B(36) s
Keywords: (3GdJhMjO hGdedd hGdfMds